The Locating Chromatic Number of Zigzag Graph Z_n - Vella Sagita Putri; Des Welyyanti; Haripamyu (Department of Mathematics, Faculty of Sciences and Technology, UIN Syarif Hidayatullah, 2025)
The locating chromatic number is a concept developed from vertex coloring and the partition dimension of a graph, first studied by Chartrand et al. (2002). A connected graph G is said to have a locating coloring when each vertex is assigned a color such that the resulting color code defined by its distances to every color class is unique. The minimum number of colors that satisfies this condition is known as the locating chromatic number, denoted by χ_L (G). This study investigates the value of χ_L for the zigzag graph Z_n with n≥3. Although colorings have been studied for various families of graphs, no explicit characterization of zigzag graphs has been established. Our analysis shows that Z_3 has a locating chromatic number of 3, while for all n≥4, the value increases to 4. These results provide the first complete characterization of locating colorings on zigzag graphs and contribute to the broader study of location-based parameters in graphs with structured topology.Keywords: Locating chromatic number; Zigzag graph; Color code. AbstrakBilangan kromatik lokasi merupakan konsep pengembangan dari pewarnaan titik dan dimensi partisi suatu graf yang pertama kali dikaji oleh Chartrand dkk (2002). Sebuah graf terhubung Gdikatakan memiliki pewarnaan lokasi apabila setiap titik diberi warna sedemikian rupa sehingga kode warna yang dibentuk berdasarkan jaraknya terhadap setiap kelas warna bersifat unik. Banyaknya warna minimum yang memenuhi kondisi tersebut disebut bilangan kromatik lokasi, dilambangkan dengan χ_L (G). Penelitian ini mengkaji nilai χ_L pada graf zig-zag Z_n untuk n≥3. Walaupun sejumlah keluarga graf telah diteliti sebelumnya dalam konteks pewarnaan lokasi, graf zig-zag belum pernah memperoleh karakterisasi yang jelas. Hasil analisis menunjukkan bahwa Z_3 memiliki bilangan kromatik lokasi adalah 3, sedangkan untuk semua n≥4, nilai tersebut menjadi 4. Temuan ini memberikan karakterisasi lengkap pertama untuk pewarnaan lokasi pada graf zig-zag dan memperkaya kajian mengenai parameter lokasi pada graf dengan struktur khusus.Kata Kunci: Bilangan kromatik lokasi; Graf zig-zag; Kode warna. 2020MSC: 05C12, 05C15.